2021
DOI: 10.1002/jgc4.1517
|View full text |Cite
|
Sign up to set email alerts
|

Telegenetics: The experience of an Indian center (Centre for Human Genetics) during the COVID‐19 pandemic

Abstract: With the spread of the COVID-19 pandemic, access to health services of all kinds has been severely challenged everywhere. Medical professionals in all specializations including genetic medicine have struggled to keep their services going. Our center, located in Bengaluru, is a tertiary clinic offering genetic services to approximately 2000 families annually. We have adopted telegenetics as a means of connecting with patient families during these difficult times. We describe here our experience in providing tel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…However, they preferred in-person GC for first (79.4%) and TGC for follow-up (60.6%) visits rather than telemedicine as an entire alternative model. A study from India also reported that 87% of the patients were satisfied with TGC services, but 74% of them preferred face-toface appointment (Rao et al, 2021).…”
Section: Tele-genetics Development In Asiamentioning
confidence: 99%
“…However, they preferred in-person GC for first (79.4%) and TGC for follow-up (60.6%) visits rather than telemedicine as an entire alternative model. A study from India also reported that 87% of the patients were satisfied with TGC services, but 74% of them preferred face-toface appointment (Rao et al, 2021).…”
Section: Tele-genetics Development In Asiamentioning
confidence: 99%
“…Several studies have been published globally about the impact of the pandemic on genetic services. [1][2][3][4][5] A review on telegenetic services showed high acceptability for it in underserved communities, with reduced travel and costeffectivity being major advantages. With a critical shortage of genetic experts in the country, combined with a mammoth population of 1.3 billion, over half of whom live in rural areas, there is very little scope for access to genetic services.…”
Section: Introductionmentioning
confidence: 99%